Sistema de gestão e os critérios de excelência do prêmio nacional de qualidade - PNQ: um instrumento de avaliação para o segmento educação - Bezerra, Marlene Jesus Soares (2002)
The objective these text is to propose a instrument to check the results, the perforrn and the continuous learning of the education segment. After theorical studies about methodologies of evaluation using the exceilence criterions of Prêmio Nacional da Qualidade PNQ 2001, adapted for education. The objective of using these instrument is to create a standard to check the results of management in the schools. The results are the answers of research made in 25 (twenty five) schools, public and private schools of high level in Estado do Rio de Janeiro.